Identification of a Bitter-Taste Receptor Gene Repertoire in Different Lagomorphs Species - Ferreira, Ana M.; Marques, Andreia T.; Fontanesi, Luca; Thulin, Carl-Gustaf; Sales-Baptista, Elvira; Araújo, Susana S.; Almeida, André M. (Frontiers in Genetics, 2016)
The repertoires of bitter taste receptor (T2R) gene have been described for several animal species, but these data are still scarce for Lagomorphs. The aim of the present work is to identify potential repertoires of T2R in several Lagomorph species, covering a wide geographical distribution. We studied these genes in Lepus timidus, Lepus europaeus, Oryctolagus cuniculus algirus, Romerolagus diazi and Sylvilagus floridanus, using Oryctolagus cuniculus cuniculus as control species for PCR and DNA sequencing. We studied the identities of the DNA sequences and built the corresponding phylogenetic tree. Sequencing was successful for both subspecies of Oryctolagus cuniculus for all T2R genes studied, for five genes in Lepus, and for three genes in Romerolagus diazi and Sylvilagus floridanus. We describe for the first time the partial repertoires of T2R genes for Lagomorphs species, other than the common rabbit. Our phylogenetic analyses indicate that sequence proximity levels follow the established taxonomic classification.